Clinical implications of the morphological features of central pulmonary artery thromboemboli shown by transoesophageal echocardiography. Issue 1 (July 1994) - Chan, R K; Johns, J A; Calafiore, P
Abstract : OBJECTIVES–To illustrate the use of transoesophageal echocardiography in the detection of the morphological features of central pulmonary artery thromboemboli and their clinical implications. DESIGN–Review of five cases of central pulmonary artery thromboemboli detected by transoesophageal echocardiography. SETTING–University teaching hospital. PATIENTS–Five patients (three men and two women) admitted under general medical units. RESULTS–Central pulmonary artery thromboemboli were detected by the use of transoesophageal echocardiography in all the patients presented. Presentations were acute, subacute, or chronic. The morphological features of the thromboemboli on transoesophageal echocardiography were used to correlate with the time course of the illness, and to guide treatment. Two patients received thrombolytic treatment, one patient was treated with anticoagulation alone, and two patients had inferior vena caval filters implanted. CONCLUSIONS–Transoesophageal echocardiography is an alternative diagnostic tool in the detection of central pulmonary artery thromboemboli. Morphological features of central pulmonary thromboemboli on echocardiography can provide useful information that may help to guide treatment.